THE ABILITY OF THE TENTH GRADE STUDENTS OF SMAN 1 RAMBAH IN WRITING RECOUNT TEXT - Aliffiona Suci; Rumiri Aruan; Eliwarti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed to investigate the ability of the tenth grade students of SMAN 1 Rambah in writing recount text. The problem discussed in this study is : How good is the level of the tenth grade students ability in writing recount text? The methodology of this research is descriptive quantitative research. The data of the study are recount texts made by the tenth grade students of SMAN 1 Rambah. In this study, the instrument used in this research was a written test in the form of a report of science experiment. There are 7 classes for population of this research consists of 174 students. Since the material which investigated was a report of science experiment, so the writer took 69 students (X IPA 1, X IPA 2, X IPA 3) as the sample of the research selected by purposive sampling. The data of this research were collected by conducting a written test. The writer asked the students to write the scientific report based on the experiment that they have done. It might be chemistry, biology, or physics experiment. The results of data analysis showed the mean score of students’ ability in writing recount text was 70.71. Based on the data analysis, it can be concluded that the ability of tenth grade students of SMAN 1 Rambah in writing recount text is in good level based on Brown’s analytical scale for rating composition tasks. In relation with the result of the study, it can be suggested (1) for the students, they need more practice in writing and should pay attention to grammar and mechanics aspects, since the score of these writing aspects were low, (2) it is better to English teachers to apply appropriate methods and techniques in teaching recount text in class to the students so that they are able to write recount text well, and (2) for the next researchers, it is hoped that this research can be a source of literature review to conduct similar researches.Keywords: Writing, Ability, Students’ Writing Ability, Recount Text